Penyuluhan Mengenai Hukum Perkawinan di Gereja Katolik Santo Paulus Miki Salatiga - Indirani Wauran; Oliviani Yanto (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2022)
Marriage is an inner and outer bond between a man and a woman as husband and wife to form a happy and eternal family (household) based on God Almighty. Marriage is an event that often occurs in human life and society; however, people often do not understand marriage law. Therefore, it is crucial to conduct legal counseling regarding marriage so that the public understands the legal rules surrounding the marriage, including the principles of marriage, the legal requirements of marriage, and the legal consequences of marriage. This counseling aims to understand marriage law, especially one based on the Indonesian Marriage Law. Therefore, the method presents marriage law material, followed by a question-and-answer session. This counseling was online using zoom.us, attended by congregation of Saint Paul Miki Church in Salatiga. This activity provides benefits in the form of increased knowledge and understanding of marriage law for unmarried and married participants.